Extended Telemedical Consultation using Arden Syntax Based Decision Support, Hypertext and WWW Technique - Karlsson, D.; Ekdahl, C.; Wigertz, O.; Shahsavar, N.; Gill, H.; Forsum, U. (Methods of Information in Medicine, 1997)
There is an obvious need for geographic distribution of expert knowledge among several health care units without increasing the cost of on-site expertise in locations where health care is provided. This paper describes the design of a knowledge-based decision-support system for extended consultation in clinical medicine. The system is based on Arden Syntax for Medical Logic Modules and hypertext using World Wide Web technology. It provides advice and explanations regarding the given advice. The explanations are presented in a hypertext format allowing the user to browse related information and to verify the relevance of the given advice. The system is intended to be used in a closed local network. With special precautions regarding issues of safety and patient security, the system can be used over wider areas such as in rural medicine. A prototype has been developed in the field of clinical microbiology and infectious diseases regarding infective endocarditis.
Keywords: Knowledge-based system; DSS; Arden Syntax; Hypertext; WWW